Advanced computer-aided fixture design - Rong, Yiming, 1958- (Elsevier, 2005)
Fixtures--the component or assembly that holds a part undergoing machining--must be designed to fit the shape of that part and the type of machining being done. This book discusses the fundamentals of Computer-Aided Fixture Design (CAFD) techniques and covers fixture planning, fixture design (both modular and dedicated fixtures), fixture design verifications, and the overall integration with CAD/CAM. The book shows how CAFD may lead to a significant reduction of product and process development time and production cost, and how CAFD can increase quality assurance through simulation and science-based technical specification and cost estimation in business quoting, especially in current supplier-based manufacturing. It also provides case study examples.